The Study of Dielectric and Microstructure Properties for Iraqi Kaolin Under the Effects of Binder and Calcinations. - Rasin, F.; Al-Khafaji, R. (Iraqi Journal of Science, 2024)
The calcination treatments and a binder of poly acrylic acid PAA (1wt%)effects on kaolinite particles were investigated through dielectric properties at1MHz ,quantitative analysis of X-ray diffraction and microstructure. The calcinatedsamples at 850°C/3hr and fired at 1350°C/2hr were revealed decrease in broadening(Full Width at half maximum) FWHM and increase of dielectric constant.